Witold Kieżun – an extraordinary person (Economic and Political Thought, 2021)
The article reports on the almost 100-year life of the outstanding scientist prof. Witold Kieżun. The article describes his insurgent activity, imprisonment in a labor camp during the Stalinist era, return to study and work in a bank, at the Polish Academy of Sciences, at the University of Warsaw, at Quebeck University in Canada, at the Kozminski University, and the UN’s expert activity in African countries.
Keywords: Kieżun, praxeology, management, Warsaw Uprising, the national bank of Poland, war and post-war experiences